Simian virus 40 and polyoma virus stimulate overall cellular RNA and protein synthesis. - Khandjian, E W (1980)
In lytic infection with simian virus 40 and polyoma virus of monkey and mouse cells in tissue culture, synthesis of the viral tumor (T) antigens (T antigens) is rapidly followed by a mitogenic response of the host cell. The latter begins with virus-induced stimulation of overall cellular RNA and protein synthesis, leading to a substantial increase in cytoplasmic and nuclear RNA and protein. Stimulation begins within 1 hr after onset of T-antigen synthesis and also occurs if virus-induced DNA synthesis is blocked by metabolic inhibitors. The broad spectrum of biological and molecular effects induced by simian virus 40 and polyoma virus is, at least phenotypically, reminescent of the pleiotropic impact exerted on target cells by nonviral mitogens and by certain growth-promoting steroid and polypeptide hormones.